(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In the paper we have discussed about Wireless sensor network and its design anddevelopment aspects while keeping security of information into mind. From the primary informationpoint-of-view we discussed about network and wireless sensor network, primary characteristics of WSN.Different network topologies are explained in this paper and need of network security while sending andreceiving data is also explained. The art of hiding text in some scrambled text is also explained into thispaper under the section cryptography.